Social Issues and Problem-based Learning in Sociology: Opportunities and Challenges in the Undergraduate Classroom - Eglitis, Diana; Buntman, Fran; Alexander, Dameon (TRAILS: Teaching Resources and Innovations Library for Sociology, 2016)
This article discusses the use of problem-based learning (PBL) in the undergraduate sociology classroom. PBL shifts students from the role of passive listeners and learners to active knowledge builders and communicators through the use of concise and engaging social problem cases. PBL creates opportunities for building substantive area knowledge, research skills, and problem-solving capacities and fosters student enjoyment. This teaching note describes the key characteristics of PBL, discusses practical approaches to its use in a variety of sociology courses, and offers sample case studies. We evaluate student experiences with PBL and consider its broader applicability.